Effects, possibilities and advantages of complex іnfusive preparation sorbilactum - Chepky, L. P.; Gavrish, R. V.; Chitaeva, G. E. (Ukrainian Neurosurgical Journal, 2007)
In the review the state and problems of infusive therapy for today are described; comparison of different preparations for infusions is given. The application of sorbilactum — complex medicine on the sorbitolum basis — is considered in details; effects, possibilities and advantages of preparation, and also results of clinical researches are described.